Analisis Metode Demonstrasi Pembelajaran IPAS Perubahan Wujudbenda Kelas IV Mi Al-Ma’arif Drono - Upita Ayu Widayanti; Afifah Fatin Pratiwi; Nela Rofisian (CV. ITTC INDONESIA, 2023)
This study aims to determine how to apply and the impact of usi ng demonstration methods on science learning changes in the form of objects in class IV MI AL Ma'arif Drono. This type of research uses descriptive qualitative methods. The instruments used are documentation, observation, observation and interviews. The subjects of this study were 11 students of grade IV of MI Al Ma'arif Drono for the academic year semester 2023/2024. The result of this study is that by using the demonstration method students better understand the material provided, create a learning atmosphere that is fun and makes students more active in learning